FDI policies in Europe in the aftermath of the 2008+ crisis - Götz, Marta (Economics and Business Review, 2016)
In the aftermath of the 2008+ crisis economic protectionism was feared to return. Financial turbulence, trade imbalances, instability of fiscal policies and labour market deterioration made intervention by the state justified. To cushion the blow various measures were launched. Whereas major economic policies such as the fiscal, monetary or labour market policies were adjusted, little is known about possible modifications in other, less popular, areas of government activity such as the policy on foreign direct investment (FDI). By combining available sources – mainly international scoreboards and rankings – this article sought to classify the member states of the European Union (EU MS) according to their policies pursued in respect of outward and inward foreign direct investment (OFDI and IFDI) after 2008. The main value added could be seen in: (i) the selection, compilation and assessment of various indicators proposed as the most suitable approximation of FDI policies; (ii) the coverage of all the EU members without a priori focusing only on some cases; and (iii) touching upon OFDI which is rather rare in FDI literature dominated by studies on IFDI. The major obstacle which may impair the quality of the research outcome was the lack of proper indicators i.e. lack of variables which can stand for genuine FDI policy. The results obtained indicate the dominance of rather more restrictive attitudes in respect of inward and outward FDI amongst the EU member states in the aftermath of the 2008+ crisis.